ANALISIS EFEKTIVITAS IKLAN RAMAYANA BERBASIS EPIC MODEL PADA MEDIA SOSIAL YOUTUBE - Siti Fatimah; Firda Nosita (Ultima Management : Jurnal Ilmu Manajemen, 2019)
The research aims to measure the effectiveness of the Ramayana advertisement 'Eid on the udique planet' on YouTube. This study used online questionnaire and obtained from 96 students of Pancasetia School of Economics (STIE Pancasetia) Banjarmasin who have seen the Ads. The study use the EPIC Model by The Nielsen Company. They are empathy, persuasion, impact, and communication. The EPIC analysis results for each dimension are 3.52 for empathy, 3.51 for persuasion, 3.42 for impact and 3.57 for communication and the EPIC rate is 3.505. The Ads is effective to audience and proven to provide information and interesting message, which can drive someone to take the further behavior, i.e. buying decision.